Conflict Management Styles In Software Engineering - Al-Bazi, Sogeta; Pattewar, Pallavi (My University, 2024)
In software engineering teams, interpersonal conflicts are inevitable and can significantly impact project outcomes and team dynamics. These conflicts can arise from a variety of causes, including when the needs and desires of individuals or parties contradict. To resolve these conflicts, effective management strategies are required to ensure successful project delivery and optimal team functionality. The Thomas- Kilmann Conflict Mode Instrument (TKI) is widely utilized to evaluate conflict management approaches, based on two principal dimensions: Assertiveness and Cooperativeness. These dimensions define five distinct conflict management styles: Avoiding, Compromising, Accommodating, Competing, and Collaborating. This study examines the distribution of conflict management styles among software engineers, with a specific focus on gender differences and the distinctions between students and practitioners, by using the TKI model. It also examines their level of awareness regarding these styles. We employed a mixed-methods approach, integrating a quantitative survey using the TKI with qualitative interviews. We analyzed responses from 82 survey participants and conducted 10 in-depth interviews. We used Bayesian data analysis to interpret the survey results and applied thematic analysis to the interview data. The findings reveal that Collaborating style is predominantly favored across all demographics. However, notable differences were observed: students exhibited a significant preference for the Avoiding style, indicative of their less confrontational approach, whereas practitioners tended towards Accommodating and Compromising, reflecting their more seasoned conflict resolution skills. Gender analysis showed females have higher tendency toward Collaborating and Compromising style, while that males were more inclined towards Competing style. We found no significant differences between genders in the Avoiding and Accommodating styles. Qualitative insights confirm that while the Collaborating style is preferred, many individuals adapt their conflict management strategies based on situational demands, interpersonal interactions, and organizational hierarchy. The results emphasize the importance of tailored training programs in educational institutions and professional organizations.
Keywords: Conflict management styles, software engineering, Thomas-Kilmann Conflict Mode Instrument, gender differences, professional experience, Bayesian analysis, Thematic analysis.